Progressive taxation and (in)stability in an endogenous growth model with human capital accumulation - Aleksandar Vasilev (Economics and Econometrics Research Institute (EERI), 2016)
We show that in an endogenous growth model with human accumulation calibrated to Bulgarian data under the progressive taxation regime (1993-2007), the artificial economy exhibits equilibrium indeterminacy. These results are in line with the recent findings in Chen and Guo (2015) in the context of an AK endogenous growth model. Also, the findings are in contrast to Guo and Lansing (1988) who argue that progressive taxation works as an automatic stabilizer. Progressive taxation in our setup leads to equilibrium indeterminacy. This indeterminacy result could explain, at least partially, why the economic performance under the progressive taxation regime in Bulgaria was not impressive.
Keywords: E32; E62; O41; 330; Progressive Income Taxation; Endogenous growth; Human capital; Equilibrium (In)determinacy